Effects of a healthy diet based on seed-rich vegetables on the gut microbiota and intrinsic brain activity in perimenopausal women: A pilot study on cognitive improvement - Caihui Guo; Zhenliang Xiong; Lin Yang; Mingxian Bai; Yi Zhu; Xianchun Zeng (Scientific Reports)
Abstract Brain functional changes and gut microbiota dysbiosis have been observed in perimenopausal syndrome (PMS). We evaluated the effects of a plant-based daily diet enriched with Raphanus sativus L. (RSL, radish seed) on the gut microbiota composition, gastrointestinal symptoms, resting-state local spontaneous brain activity, and neuropsychology in perimenopausal women. For 12 weeks, the participants were instructed to adhere to a controlled, Raphanus sativus L.-rich plant-based diet (a mean RSL intake of 5 g/day). Two test days were organized: before and after the nutritional intervention. The fecal microbiota composition, gastrointestinal symptoms, resting-state brain function, and neuropsychology were assessed twice. A longitudinal single-arm study was conducted on 24 perimenopausal women. The Montreal Cognitive Assessment (MoCA) scores tended to improve in the visuospatial/executive function subitem and in the total score after the diet. The participants presented elevated amplitude of low-frequency fluctuation (ALFF) values in the left middle occipital gyrus, the left precentral gyrus, and the left middle cingulum gyrus. The abundances of the phyla Synergistetes and Verrucomicrobia were positively correlated with the ALFF values of the left middle occipital gyrus, left precentral gyrus, and left middle cingulum gyrus. These data suggest that specific gut microbes may modulate intrinsic brain activity and cognitive function in perimenopausal women. A plant-based RSL-rich diet has beneficial effects on the gut microbial composition and brain function of perimenopausal women.